2D versus 3D roadmap for uterine artery catheterization: impact on several angiographic parameters. (February 2014) - Maleux, Geert; Michielsen, Koen; Timmerman, Dirk; Poppe, Willy; Heye, Sam; Vaninbroukx, Johan; Bosmans, Hilde
Background: Three-dimensional (3D) roadmap is a recently developed imaging technique used to guide diagnostic and interventional catheter-directed procedures and mainly evaluated for neurovascular procedures. Few data with regard to efficacy and radiation dose are currently available in literature. Purpose: To evaluate the use of 3D roadmap technique as compared with the conventional two-dimensional (2D) roadmap for uterine artery catheterization and embolization during uterine fibroid embolization and assess the potential impact on radiation dose, contrast load, and total procedure time. Material and Methods: In this prospective study, 40 patients were randomly assigned to the 2D or 3D roadmap technique for uterine artery catheterization. Demographic data, specifically the patient's age, weight, height, pelvic circumference, and total uterine and fibroid volume were recorded. Exposure parameters, contrast load, and procedure time were recorded and organ doses for ovaries and uterus were calculated. Results: Demographic data did not differ between the groups. Catheterization and embolization of both uterine arteries were feasible in all patients, although in one patient in the 3D group, a focal dissection of the proximal uterine artery occurred. No significant difference in estimated ovarian dose was found in the 3D versus 2D group ( P = 0.07). Total procedure time was shorter in the 2D group ( P = 0.01) and no difference in total contrast load was seen ( P = 0.17). Conclusion: Both roadmap techniques are effective imaging-guided tools for uterine artery catheterization, without difference in terms of radiation exposure or contrast load. The total procedure time is shorter in the 2D group.